Information technology-based versus face-to-face cognitive-behavioural therapy for anxiety and depression: A systematic review and meta-analysis - Chow, Dilys Yan-wing; Jiang, Xinchan; You, Joyce H.S. (Journal of affective disorders, 2022)
We aimed to systematically review the efficacy of information technology-based cognitive behavioural therapy (ICBT) versus face-to-face cognitive behavioural therapy (FCBT) for management of anxiety and depression in adult patients. Systematic literature search for clinical trials comparing ICBT to FCBT in adults diagnosed with anxiety or depression was conducted. Quantitative analyses were performed to examine the efficacy of ICBT versus FCBT. Primacy outcome was change in symptom severity. A total of 11 publications (10 studies and 896 participants) were included. The pooled effect size of ICBT versus FCBT did not find significant difference for post-treatment anxiety or depressive symptoms severity (Hedges' g = −0.07; 95% CI = −0.20 to 0.06), and ICBT was non-inferior to FCBT (at Cohen's d = 0.3). Maintenance of treatment efficacy also showed no significant difference between ICBT and FCBT at 6 months (g = −0.14, 95% CI = −0.42 to 0.14) and 12 months (g = −0.05, 95% CI = −0.41 to 0.32) post-treatment. Adherence rate was lower in ICBT than FCBT but did not achieve statistically significance (61% vs 88%; RR = 0.86, 95% CI = 0.74 to1.00). Results were not affected by study quality. The examination of study heterogeneity was limited by the small number of studies. We found non-inferior performance of ICBT versus FCBT in reducing symptoms in patients diagnosed of anxiety or depressive disorders. With the social-distancing measures amid COVID-19 pandemic, service providers should give serious consideration with great caution in the decision-making process of offering ICBT to patients. •Cognitive behavioural therapy (CBT) is a key treatment for anxiety and depression.•CBT can be delivered by face-to-face (FCBT) and information technology (iCBT).•A systematic and meta-analysis evaluated studies directly comparing iCBT and FCBT.•Findings showed performance of ICBT was non-inferior to FCBT.